(untitled) (European Journal of Behavioral Sciences, 2021)
The paradigm of economic rationality is eroded by criticism from related behavioral disciplines, especially psychology. Neuroeconomics is a new multidisciplinary approach to behavioral economics. Neuroeconomics orders the Big5 Taxonomy by risk-will into a pluralist behavioral economics (PBE) that changes the classical and develops new domains of economic behavior: Firstly, consumer behavior is not sovereign but formed by group standards centering Open-mindedness. The rational consumer standard is now “Simple Living” as an alternative to consumerism. Secondly, the prototype of open-mindedness in production life is identified as the Pilot-in-the-plane entrepreneur that expands the production scope far beyond maximization of profit to include characteristics such as pragmatism, versatile team composition and perseverance to overcome obstacles. Thirdly, stress-management by meditative in-depth relaxation is evidenced as a complement to fitness. Fourthly, gender economics is supported by neuroeconomic findings on mental gender differences. Fifthly, Neuroeconomics explains the qualitative value of industrialization as “Rise of the Creative Class” due to liberal upbringing, broader and better tertiary education and more business options. The Discussion focuses on spillovers from PBE to the democratic culture. The option is to moderate historical economic-political polarization to that of complements with a broader population base.